2021
DOI: 10.2991/assehr.k.210423.081
|View full text |Cite
|
Sign up to set email alerts
|

Creativity, Critical Thinking, and Academic Performance in Students University During Virtual Learning

Abstract: Optimization of virtual learning is not only supported by the availability of adequate facilities but also through developing student potential in the aspects of creativity and critical thinking. Both of these aspects are absolutely needed by students to adapt to the learning process, one of which will also affect their learning achievement improvement. This study aims to look at the relationship between creativity, critical thinking, and student academic performance during online learning. The quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Hence the instructors do not need to provide customized feedback to each student. (Prakoso et al, 2021) found a positive relationship between creativity and critical thinking disposition. These two factors also positively influenced the academic performance of the students.…”
Section: School Administration: Violence Among Elementary School Stud...mentioning
confidence: 90%
“…Hence the instructors do not need to provide customized feedback to each student. (Prakoso et al, 2021) found a positive relationship between creativity and critical thinking disposition. These two factors also positively influenced the academic performance of the students.…”
Section: School Administration: Violence Among Elementary School Stud...mentioning
confidence: 90%
“…Hal ini tampak dari berbagai penelitian yang menunjukkan hubungan yang signifikan antara kemampuan berpikir kritis serta prestasi akademik. Sebuah penelitian yang dilakukan oleh Prakoso, dkk , mengungkapkan bahwa siswa yang berpartisipasi dalam kegiatan berpikir kritis menunjukkan peningkatan tingkat pemahaman, analisis, dan sintesis, sehingga menghasilkan peningkatan hasil belajar (Prakosa, Ramdani, Felisima. T, & Riandika, M, 2021).…”
Section: Hubungan Berpikir Kritis Dengan Kompetensiunclassified
“…This translates to the employment of avant-garde methods to impart religious concepts to students. Creativity can also foster critical thinking and deepen students' comprehension of religion (Prakoso et al, 2020). By applying creativity in teaching Islamic education, educators can employ innovative techniques such as interactive games, religion-centric projects, and other imaginative activities to fully engage students in the learning process.…”
Section: The Role Of Creativity In Teaching Islamic Educationmentioning
confidence: 99%